Mechanics of Aero-structures - Nair, Sudhakar (Cambridge : Cambridge University Press, 2015)
Mechanics of Aero-structures is a concise textbook for students of aircraft structures, which covers aircraft loads and maneuvers, torsion and bending of single cell, multi-cell and open thin-walled structures. Static structural stability, energy methods, and aero-elastic instability are discussed. Numerous examples and exercises are included to enhance the students' facility with structural analysis. This textbook is meant for third- and fourth-year undergraduate students in the aerospace and aeronautical engineering programs, and the material included can be covered in a one semester course. A sufficient number of figures are included for the clarity of the subject matter. The book begins with a description of aerodynamic loads to motivate students, and includes an in-depth description of energy methods - an essential topic.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Aerodynamics